A five-year follow-up of animal use at Marmara University School of Medicine - (:unkn) unknown (My University, 2002)
Objective: To improve the standards of animal welfare, as well as scientific quality, good education and training is necessary for implementing reductions, refinements and replacement alternatives (3Rs). Ethical justification of laboratory animal use by our institutional committee has served to achieve a greater acceptance of the concept of humane experimental techniques. Methods: In this retrospective study, a five year follow-up of data collected within Institutional Animal Use and Care Committee was evaluated. Results: Our results show that reviewing the protocols and giving feedback to researchers has an educational value in improving the skills and attitude of persons involved in the design and performance of animal experiments. Conclusion: Therefore, while giving education or training, the use of laboratory animals should be reviewed thoroughly, not only for the application of the 3Rs but also for further education of those involved in or responsible for animal use.
Keywords: 3Rs; Animal ethics; Animal welfare; Pain